(untitled) (Global Journal of Human-Social Science, 2022)
Menstruation is a phenomenon unique to girls However it has always been surrounded by taboos that lead to the exclusion of women from many spheres of life In rural India the topic is still taboo One of the biggest challenges that women face is not being educated and not having the resources to get sanitary pads The present research study aims to evaluate the effectiveness of a self-formulated campaign called Spot On Off to raise awareness about menstrual hygiene among females belonging to three different age groups 8-15 16-35 36-60 with most of the girls from the age group 16-35 They live in the rural area of Mewat in Haryana India A survey was conducted with 300 female respondents Post the survey an awareness workshop was carried out where videos of gynaecologists explaining what menstruation is was shown A post-survey was conducted to assess the effectiveness of the campaign The respondents awareness showed a significant increase from 2 19 to 5 54 out of 10 on average The study also found out that awareness had a 19 impact on the liking of reusable pads